Observation of Λb0 → Λc+ D̄(*)0 K- and Λb0 → Λc+ Ds*- decays - Aaij, Roel; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; Kubat, Jakub; et al. (The European physical journal. C, Particles and fields, 2024)
The decays Lambda(0)(b) -> Lambda(+)(c) (D) over bar (()*()0) K- and Lambda(0)(b) -> Lambda(+)(c) D-s*(-) are observed for the first time, in proton-proton collision data at root s = 13TeV, corresponding to an integrated luminosity of 5.4fb(-1) collected with the LHCb detector. Their ratios of branching fractions with respect to the Lambda(0)(b) -> Lambda(+)(c) D-s(-) mode are measured to be B(Lambda(0)(b) -> Lambda(+)(c) (D) over bar (0) K-)/B(Lambda(0)(b) -> Lambda(+)(c) D-s(-)) = 0.1908(-0.0034-0.0018)(+0.0036+0.0016) +/- 0.0038, B(Lambda(0)(b) -> Lambda(+)(c) (D) over bar*(0) K-)/B(Lambda(0)(b) -> Lambda(+)(c) D-s(-)) = 0.589(-0.017-0.018)(+0.018+0.017) +/- 0.012, B(Lambda(0)(b) -> Lambda(+)(c) D-s*(-))/B(Lambda(0)(b) -> Lambda(+)(c) D-s(-)) = 1.668 +/- 0.022(-0.055)(+0.061), where the first uncertainties are statistical, the second systematic, and the third, for the Lambda(0)(b) -> Lambda(+)(c) (D) over bar (()*()0) K- decays, are due to the uncertainties on the branching fractions of the D-s(-) -> K- K+ pi(-) and (D) over bar0 -> K+ pi(-) decay modes. The measured branching fractions probe factorization assumptions in effective theories and provide the normalization for future pentaquark searches in Lambda(0)(b) -> Lambda(+)(c) (D) over bar (()*()0) K- decay channels.